Labour market institutions - the problem of definitions and measurement - Sordyl, Marta (Ekonomia i Prawo. Economics and Law, 2024)
Motivation: Despite a wealth of research the role of labour market institutions (LMIs) remains controversial. The problem is on the increase lately because of socio-economic transformation affecting the functioning of labour markets. One of the explanations of the problem might be the lack of precise definitions and proper measures of LMIs, especially informal ones, that could be used in econometric research. Aim: The aim of the paper is twofold. First, to follow the evolution of the concept of LMI measures in economic literature, both in the theoretical context and in empirical application. Second, to compare different measures of employment protection legislation (EPL) and assess their effectiveness in capturing the quality of workers’ protection. The analysis takes an institutional perspective which assumes that LMIs are a means to solve the problem of market inefficiencies rather than a source thereof. Results: The paper identifies inadequacies in the way LMIs are measured and used in empirical research. Keywords: labour market policies, employment protection, institutional economics JEL: J08; J83; E02